Metallurgical influence of separated endodontic instruments on the retrieval capability of katana-sword-like ultrasonic tip under different lubricants: In vitro study - Omnia Abdel Hakim; Nihal Ezzat Sabet; Heba Ahmed Elasfouri (Saudi Endodontic Journal, 2024)
Introduction: Ultrasonic retrieval is a time-consuming procedure sacrificing considerable amounts of dentin. This study aimed to assess the retrieval capability of katana tip on different alloys under different lubricants regarding dentin thickness and retrieval time. Materials and Methods: Extracted premolars were used to reach 40 samples. The apical 4 mm of X2 ProTaper Next and A1 Neoniti instruments were fractured, and katana tip was utilized for retrieval, using ethylenediaminetetraacetic acid or olive oil as intracanal lubricants. Dentin thickness was assessed using cone-beam computed tomography, and the time of retrieval was recorded. Results: There was no significant difference in the retrieval capability among the groups. Different alloys and lubricants had no significant effect on dentin thickness. However, olive oil significantly reduced the retrieval time. Conclusion: Katana tip proved to be efficient enough to retrieve apically separated instruments in curved canals, with instrument’s metallurgical makeup presenting minimal effect on its capability. Katana tip and high-viscosity lubricants reduced the retrieval time, which might reduce the dentin removal amount.